A study on the relationship between total quality management (TQM) practices among employees at administrative department in UiTM Jengka Pahang / Amila Suhaila Ammaran - Ammaran, Amila Suhaila (2016)
There is a recent and vulnerable debate in the literature regarding the influence of total quality management (TQM) to innovation. Several studies have been review at what area organizations that implement TQM practices and approaches tend to be more innovative (Prajogo & Sohal, 2001, 2006a, b; Singh and Smith, 2004; Molina et aI., 2007; Sa' & Abrunhosa, 2007). The contribution of TQM to innovation has not been realized sufficiently in former research (Prajogo & Sohal, 2003a), especially, empirical studies are occasional. The review on the relationship between TQM and innovation do not seem very commonly in the literature. Basically, there are only a lesser number of such literatures which is supported by theoretical concepts or by empirical proof. The existing studies indicate a complex relationship (Bon & Mustafa, 2012 in press). The complication appears from the variety of TQM practices and variety of its aspect and, on the other hand, from diversity typology of innovation. Agreeing to Prajogo and Sohal, (2001) there are conflicting disagreements fearing the relationship between TQM and innovation. Total Quality Management-Innovation literatures unveil both positive and negative interpretations of the scholars on the relation between Total Quality Management and innovation. There are two conflicting schools of thought concerning relationship between TQM and innovation. One school believes that TQM supports innovation, suggesting that organizations that implement TQM will be effective in innovation. The substitute school represented by Wind and Mahajan (1997), Tidd et al. (1997), Slater and Narver (1998), Kim and Marbougne (1999) argues that TQM disrupt innovation. The main argument issue is in the disagreement whether the nature of TQM practices does support innovation or not.